RAQAMLASHTIRISH JARAYONIDA AXBOROT XAVFSIZLIGINI TA’MINLASHNING METODIK ASOSLARI - Anvar Kutlimuratov (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article highlights the methodological foundations of ensuring information security in the digitalization process. The concept of information security and its theoretical foundations are analyzed, and technologies and methodological approaches to ensuring security in the digital environment are considered. Also, the methodological principles used in the educational process to ensure information security are described in detail. The article provides recommendations for ensuring information security through the effective use of digital technologies.